In Search of the Reason for the Breathing Effect of MIL53 Metal-Organic Framework: An ab Initio Multiconfigurational Study - Weser, Oskar; Veryazov, Valera (Frontiers in Chemistry, 2017)
Multiconfigurational methods are applied to study electronic properties and structural changes in the highly flexible metal-organic framework MIL53(\ce{Cr}). Via calculated bending potentials of angles, that change the most during phase transition, it is verified that the high flexibility of this material is not a question about special electronic properties in the coordination chemistry, but about overall linking of the framework. The complex posseses a demanding electronic structure with delocalised spin density, antifferomagnetic coupling and high multi-state character requiring multiconfigurational methods. Calculated properties are in good agreement with known experimental values confirming our chosen methods.